Body conformation and slaughter traits in males and females of two three way experimental hybrids of free range chickens (Veterinary Science, 2017)
Univariate and multivariate characterization of male and female chickens belonging to two three-way experimental hybrids developed for producing free range chickens, in comparison with Campero INTA as the reference genotype, both in terms of a set of linear measurements recorded before slaughter as well as with four zoometric indices, revealed an at least partially independent genetic basis for shape and body size. The principal component multivariate analysis of carcass yield at slaughter plus breast, leg-thigh and abdominal fat proportions evinced the presence of sources of variation for breast and leg-thigh independent of body fat content as well as two sources of variation for breast percentage, one independent and the other negatively associated with leg-thigh proportion. Although the multivariate analysis allowed characterizing the birds of each sex in terms of some particularities of potential selective significance not apparent when using a univariate approach, differences among genetic groups within sex were not remarkable from a productive point of view. Slow-growing type birds evaluated in this study showed a good breast muscle development -unlike the old-fashioned field chickens- maintain the typical sexual dimorphism of the species and exhibit their characteristic “pheasant type” phenotype together with a variable plumage pigmentation different from pure white which identifies and distinguishes them from those hybrids usually exploited by the commercial poultry industry. Regarding slaughter traits both experimental three-way crosses can be considered similar not only between them but also when compare with the reference genetic group
Keywords: Body conformation; abdominal fat; breast; thigh; free-range chickens